2015
DOI: 10.1148/radiol.14140936
|View full text |Cite
|
Sign up to set email alerts
|

Three-way Comparison of Whole-Body MR, Coregistered Whole-Body FDG PET/MR, and Integrated Whole-Body FDG PET/CT Imaging: TNM and Stage Assessment Capability for Non–Small Cell Lung Cancer Patients

Abstract: Accuracies of whole-body MR imaging and PET/MR imaging with SI assessment are superior to PET/MR without SI assessment and PET/CT for identification of TNM factor, clinical stage, and operability evaluation of NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…Several groups have suggested whole-body PET/MR protocols for lung cancer patients, all of which contain at least 1 pulse sequence specifically tailored to the chest, and most of them with exceptionally long MR acquisition times (5-9). Ohno et al showed that coregistered PET and whole-body MR is superior to PET/CT for the staging of lung cancer patients, partly contradicting previous results for whole-body MR only (8,(10)(11)(12). Fraioli et al demonstrated that PET/MR is accurate in the assessment of NSCLC resectability, detecting the correct T stage and N stage in 74% of patients (6).…”
mentioning
confidence: 97%
“…Several groups have suggested whole-body PET/MR protocols for lung cancer patients, all of which contain at least 1 pulse sequence specifically tailored to the chest, and most of them with exceptionally long MR acquisition times (5-9). Ohno et al showed that coregistered PET and whole-body MR is superior to PET/CT for the staging of lung cancer patients, partly contradicting previous results for whole-body MR only (8,(10)(11)(12). Fraioli et al demonstrated that PET/MR is accurate in the assessment of NSCLC resectability, detecting the correct T stage and N stage in 74% of patients (6).…”
mentioning
confidence: 97%
“…Although T staging had no significance with PET/CT, the diagnostic accuracy for N stage of MR imaging including STIR fast advanced spin echo (FASE) imaging, PET/MRI, and PET/CT was 98.6% for MR imaging; 98.6% and 92.1% for PET/MRI with and without signal intensity (SI) assessment based on STIR FASE imaging, respectively; and 92.1% for PET/CT (Ohno et al 2015). In addition, the accuracy of STIR FASE imaging and PET/MRI with SI assessment was significantly higher than that of PET/MRI without SI assessment and of PET/CT (Ohno et al 2015). Moreover, sensitivity of STIR FASE imaging (100%) and PET/MRI with SI assessment (100%) were significantly higher than that of whole-body PET/MRI without SI assessment (93.8%) and of PET/CT (93.8%) (Ohno et al 2015) (Fig.…”
Section: Mr Assessment Of N Classificationmentioning
confidence: 99%
“…Fused PET/MRI improved lesion depiction, localization, and quality of diagnosis more than PET/CT in gynecologic malignancy [26]. MR signal intensity assessement on fused PET/MRI improved diagnostic accuracy for pre-operative staging more than PET/CT in lung cancer (97.1 % vs. 85.0 %, respectively) [27].…”
Section: Retrospective Image Fusion Of Pet and Mrimentioning
confidence: 99%